El clima familiar y las conductas agresivas de los adolescentes del décimo año de educación básica del instituto tecnológico nacional Huaquillas, sección vespertina del cantón Huaquillas, provincia de El Oro, 2013 - Encarnación Lanche, Franklin Leonardo (2016)
The present action research had as purpose to analyze the relationship between the family climate and the teenagers’ aggressiveness level of tenth year of basic education of Huaquillas National Technological Institute, afternoon section, El Oro province, 2013. It was a Descriptive study, with a cross-sectional and quasi- experimental design, it was based on: scientific, inductive, deductive, analytical, synthetic, dialectical and statistical methods. It was used the Climate Social Scale of R.H Moos and the Aggressiveness Scale (EGA), to a sample of 164 teenagers. The results were, the 67,68% of teenagers presented a conflictive family climate and the 34,15% expressed a physical aggression level. According to the obtained results it was concluded that there is a relationship between the family climate and the teenagers’ aggressiveness level. Therefore it was recommended to elaborate a schedule previously organized and systematized by means of workshops leaded to teenagers in order to improve the family climate and the physical aggression levels